Infected burn wound healing using Hydroxy-propyl-methyl cellulose gel containing bacteriophages against Pseudomonas aeruginosa and Klebsiella pneumoniae - Meysam Adibi; Kazem Javanmardi; Noor Al-Huda Ali A.H. Saeed; Mohammad Ali Mobasher; Javad Jokar; Abdolmajid Ghasemian; Niloofar Rahimian; Ava Soltani Hekmat (Iranian Journal of Microbiology)
Background and Objectives: Pseudomonas aeruginosa (P. aeruginosa) and Klebsiella pneumoniae (K. pneumoniae) are the two leading bacterial strains involved in wound infections. These bacteria have developed broad resistance to antibiotics, which has complicated their eradication. Additionally, the formation of a polymicrobial infection poses additional problems. Among alternative or complementary options, bacteriophages, viruses that parasitize bacterial hosts, have been promising. Materials and Methods: In this research work, bacteriophages' therapeutic effects against P. aeruginosa- and K. pneumoniae-infected burn wounds were studied. The infectious burn wound model was performed on Balb/C male mice, aged six weeks and weighing 25 ± 5 gr. The effects of the Hydroxy-propyl-methyl cellulose (HPMC) gel containing phage were investigated compared to gentamicin. All of these actions were performed in separate groups for each bacteria and mixed group of bacteria (to test multi-bacterial infections treating) and the result were compared. Results: Phages appear to be effective in gel forms. Pathologic samples of different groups confirmed therapeutic results of phages. These results at the microscopic level indicated the recovery of the tissue and the removal of the infection. Conclusion: The results of this study indicate that lytic phages are powerful biological tools for the treatment of bacterial infections in burn wounds, which can be considered as one of the alternatives for drug-resistant bacterial species and the high costs of antibiotics; though further animal and trial studies are needed. Meanwhile, the complications due to their widespread use in humans should be investigated in more details.